2018–2019 Florida Citrus Production Guide: Citrus Root Weevils - Larry W. Duncan; Michael E. Rogers; Stephen H. Futch; James H. Graham (EDIS)
Citrus root weevils represent a complex of species known to infest citrus trees and various alternate host plants in Florida. This 5-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. Written by L. W. Duncan, M. E. Rogers, S. H. Futch, and J. H. Graham, and published by the UF/IFAS Entomology and Nematology Department, May 2018.